Complete mitochondrial genome of the Greek marsh frog Pelophylax cretensis (Anura, Ranidae). (3rd May 2016) - Hofman, Sebastian; Pabijan, Maciej; Osikowski, Artur; Szymura, Jacek M.
Abstract: We sequenced the complete mitochondrial genome of the Greek marsh frog Pelophylax cretensis, a water frog species endemic to the island of Crete. The genome sequence was 17, 829 bp in size, and the gene order and contents were identical to those of previously reported mitochondrial genomes of other water frog species. This is the first complete mitogenome (i.e. including control region) described for western Palaearctic water frogs.